(De)Constructing Sanctity. Josaphat Kuntsevych and Josif Semashko's "Reversed" Historiography - Norbert Morawiec (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The article presents the phenomenon of "reversed" interpretation of Jozaphat Kuntsevych's martyrdom in the writings of a Uniate hierarch, Iosif Semashko. The article conducts an analysis of epistemologically understood metaphors created by him before and after his conversion to Orthodoxy.